Öko- és lovasturisztikai tábor komplex tervezete - Pintér Blanka (2020)
The purpose of my final examination paper is to organize an eco- and horse tourism camp for children of school age. The target group are children, who are interested in this topic and willing to do related leisure activities. The camp’s program is mostly filled with eco- and horse tourism related games and completed with team-building activities and others. My goal is environmental education of young children about the wildlife and characteristic of the Fertő - Hanság National Park. My other plan is to popularize horse-riding and to spread the academic education of horse-grooming. Both courses/trainings will be put in practice with the help of field and experience trips, and with horse-riding as well. Both the programs and activities are tightly connected with the aims of Fertő-parti Lovasklub Egyesület - where I spend technical internship – while not getting distracted by the formed lines and constructed systems, what they afford. I determine the bases of the camp and conclude the potential results while considering the different forms of tourism. After preparing the program and fulfilling my internship I came to a conclusion., that I chose well this topic and the way of processing. Faithfully to the aspect and ideology of the Fertő-parti Lovasklub Egyesület, I was able to create a camp project, that will be hopefully unforgettable and eminently useful for the participants. In parallel with the camp’s planning I made an application with cost- and profession project, to which I used Bethlen Gábor Alap application document model. The base of the application is to plan such a thematic camp which we accomplish by integrate be transborder hungarian children from neighbour countries. This will help increase the good relationship with the other country, while getting know better the other nation’s traditions and values.